The Influence of Medical and Socio-Economic Characteristics of the Population of Kazakhstan on the Frequency of Doctor Visits - Spankulova, L.S.; Nurmakhanova, M.B.; Bukatov, Y.B. (BUKETOV BUSINESS REVIEW, 2023)
Object: to find out how the frequency of visits to doctors in Kazakhstan is determined by the medical and socioeconomic characteristics of the population. Methods: a survey with 1,638 participants assessed annual doctor visit frequency using a seven-option question. For balanced data, responses were grouped into categories (first, second, seventh, and fifth and sixth combined). Additional questions captured socio-economic and medical metrics. Data collection and variable selection are detailed in the article, which employs a regression model for analysis. Findings: the authors touched upon the problem of low initiative of the population related to their health and “medical paternalism”, typical phenomena for most post-Soviet countries. As a result of the simulation, it was found that the results of the evaluation of the polynomial logit and the polynomial probit correspond to each other. Conclusions: the interpretation of the results in the polynomial model shows that any alternative is given in comparison with the base alternative, so increasing the independent variable makes the choice of the alternative more or less likely compared to the base alternative. So, the variables “Healthcare” and “Medical checkup” negatively affect the first category and positively affect the second, third and fourth categories.